STRATEGI GURU TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II MIS WORA - Sahraini, Asrini; Wahyu Mulyadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine, 1) Teacher strategies towards students’ reading ability, 2) Inhibiting and supporting factors for teacher in improving students’ reading ability. The teacher method used is quantitative. The objects studiet were homeroom teachers I, II and students of class I, II Mis wora wera district bima regency. The results of the study showet that: 1) The strategy used by teachers towards students reading ability is by using the spelling method strategy usig the basal readers method and the distar method, 2) Inhibiting ang supporting factorrs for teachers in improving students’ reading ability, the inhibiting factors for teachers are: students and the environment. While the supporting factors are: peer tutors. The conclusion shows that the teacher’s strategi in mis wora wera district towards students reading ability in class is applied by teachers by inviting students to read books, making game in between learning. Providing facilities for students, teacher accustom student to literacy firts, using the lesson plan (RPP) as a reference in the class learning proces. So it can be suggested that, in order for students reading ability to improve, develop teacher strategies in the learning process